Internal factors behind the decline of the Marinid kingdom - Ashari, Mohamad Zulfazdlee Abul Hassan; Jamsari, Ezad Azraai; Ismail, Napisah Karimah; Ahmad Safian, Nursafira; Ab Rahman, Zamri (Canadian Centre of Science and Education, 2020)
The Marinid Kingdom (1215-1465) was an Islamic government which emerged in the Maghreb during medieval time. Inheriting the rule from the Almohads, the Marinids were regarded as a strong and formidable Islamic government which once ruled the entire Maghreb and parts of al-Andalus at the height of its glory. Not unlike previous Muslim governments, the Marinid Kingdom also faced various problems and went through several conflicts which affected its stability and integrity. In fact the conflicts even caused the demise of the Marinid Kingdom in the year 1465 which saw the emergence of the Wattasids. This article is aimed at determining the internal factors which contributed to the decline of the Marinids which led to its eventual demise. This study employed a method of qualitative approach via historical study and content analysis, in particular using primary and secondary sources which focused on events which led to the demise of the kingdom. Results of this study identified several internal factors which contributed to the weakness and the eventual collapse of the Marinid Kingdom. In the present-day context, it is not impossible that the same factors can cause any Muslim countries, as a sovereign state and nation, to become weak and disintegrate should the government and the people fail to cooperate in matters regarding the stability of the country.